TRANSFORMASI KOMPETENSI GURU DENGAN PERANGKAT PEMBELAJARAN BERDIFERENSIASI INTEGRATIF: MENINGKATKAN LITERASI DAN NUMERASI SISWA - Dwipa, Nendra Mursetya Somasih; Sagita, Laela; Anggraeni, Ganung (Universitas PGRI Yogyakarta, 2025)
The ability of teachers to design learning tools is an essential component of pedagogical competence, significantly contributing to the quality of teaching and student learning outcomes. However, several challenges were identified, such as uncertainty in implementing differentiated learning, minimal integration of HOTS (Higher Order Thinking Skills) and TPACK (Technological Pedagogical Content Knowledge), and a lack of coherence among learning tools. This community service program aims to enhance teacher professionalism at SMP Negeri 14 Yogyakarta through mentoring in the development of differentiated and integrative learning tools. The implementation adopts a blended learning model, involving stages such as preparation, training, instructional material design, classroom practice, and reflection. The results showed significant improvements: 93.93% of teachers implemented innovative teaching, 75.75% had complete learning tools, 84.84% applied differentiated instruction, 87.87% incorporated HOTS, 78.79% utilized TPACK, and 87.88% optimized students’ literacy and numeracy skills. This program effectively enhanced teacher competence in designing more coherent and innovative teaching practices, supporting the improvement of education quality at the school. Keyword: differentiated, learning tools, literacy and numeracy, professionalism